A case study of LEAN application for shortest lead time in composite repair shop - Adly Ishak, Fadzil; Khudri Johari, Muhd; Dolah, Rozzeta (International Journal of Engineering and Technology, 2018)
Lean tools and applications have been adopted globally by many companies and industries such as automotive, aerospace, healthcare, pharmaceutical, shipbuilding, public services, project management and several others. The most basic of lean tools can be distinguished by the following: Value Stream Mapping (VSM), 5S and Kaizen, and many have agreed that these are the best selections in the initial approach of lean system and these techniques are part of the Y Management System (YMS) initiatives. This research is intended to make VSM as the primary working culture, which has been proven suitable to the servicing companies that conduct Maintenance, Repair and Overhaul (MRO) activities. With full cooperation from Company X Sdn. Bhd., researchers were able to review and later harmonize the implementation flow of VSM with the intentions to increase their personnelâ€™s production rate significantly. The rudder repair project involving the maintenance of Royal Military Airforceâ€™s Skyhawk aircraft has been given the opportunity to be experimented with VSM. After the analysis of all 53 personnel involved, it can be concluded that the lean implementation has considerably improved their individual performances, organizational behaviours, future work mapping and personal/team workstations. Â Â Â